THE EFFECT OF THE WISATA ALAM INDONESIA APPLICATION ON USER’S EXPERIENCE USING USABILITY TESTING AND QUESTIONNAIRE - Lase, Nidar Putri Dayanti; Telaumbanua, Yasminar Amaerita; Maru’ao, Nursayani; Harefa, Afore Tahir (Universitas PGRI Palembang, 2025)
This research aims to find out the effect of Wisata Alam Indonesia application on user experience using Usability Testing and the User Experience Questionnaire (UEQ) method. The study focuses on 6th semester students of class A from the English Education Study Program at Universitas Nias. Data were collected using a questionnaire that measures six scale: attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty and five components of usability testing: learnability, efficiency, memorability, errors, satisfaction. The research findings show that the Wisata Alam Indonesia application has a positive effect on user experience, with the highest scores in attractiveness (mean score = 4.73) and novelty (mean score = 10.15). However, areas such as efficiency (mean score = 3.65) and perspicuity (mean score = 3.19) present opportunities for improvement. The overall average score for user experience was 46.42, while the usability testing of the application revealed a mean score of 45.00. The correlation coefficient (r = 0.896) indicates a very strong positive relationship between the usability of the application (Wisata Alam Indonesia) and user experience. The hypothesis testing results support this conclusion, with the t-test showing thitung = 9.911 > ttabel = 2.063 and the F-test indicating Fhitung = 98.228 > Ftabel = 4.259, both of which confirm the rejection of H0 and acceptance of Ha. These results suggest that the Wisata Alam Indonesia application can enhance user satisfaction, but adjustments in certain usability components could further improve the experience.